Lesbische Frauen in der Arbeitswelt: The L-Word in Business - Regine Graml; Tobias Hagen; Yvonne Ziegler; Kristine Khachatryan; Ricky Astrida Herman (Frankfurt University of Applied Sciences, Fachbereich 3: Wirtschaft und Recht, 2020)
Diese aktuelle Studie untersucht die Arbeitssituation von lesbischen Frauen in Deutschland. Dabei vergleicht sie die Erfahrungen erwerbstätiger lesbischer Frauen mit denen heterosexueller Frauen und untersucht Diskriminierung im Bewerbungsverfahren von Berufseinsteigerinnen. Die Ergebnisse eines Experiments mit Bewerbungen zeigen, dass lesbische Frauen schon zu Berufsbeginn in Einstellungsverfahren Diskriminierung erleben, indem sie z.B. seltener zu Interviews eingeladen werden. Ein wichtiges Ergebnis einer gleichfalls durchgeführten Befragung unter lesbischen und heterosexuellen Frauen zeigt, dass lesbische Frauen in ihrem Arbeitsumfeld stärker Diskriminierung aufgrund des Geschlechts als Diskriminierung aufgrund der sexuellen Identität erleben. – – The current study explores the working conditions of lesbian women in Germany. It compares lesbian women's experiences to those of heterosexual women and examines the level of discrimination during job-application for women who enter professional life. The study encompasses an experimental setting, with 294 applications sent to prospective employers, where half of these applications indicated a lesbian, the other half a heterosexual orientation. Furthermore, a quantitative survey among 1.952 women, 713 of them lesbian and 1.239 heterosexual women was conducted, exploring among others the situation at the workplace, forms of discrimination experienced, salary, life satisfaction, and strategies how the women manage their sexual identity at the job. The results indicate that lesbian women do face discrimination when applying for jobs, as they are less often invited for job interviews. Another important result is that lesbian women experience stronger discrimination on the job due to their gender than their sexual orientation.
Keywords: 650